Zakat and Waqf As an Economic Development - Deva Wijayanti; Tika Widiastuti (AFEBI Islamic Finance and Economic Review, 2020)
The public  financial sector is experiencing   quite  dynamic  developments  from time totime.   Its development is  also  influenced  by the character   of the system of government  that  occurs at a certain time.  Since  the time of the  Prophet   (s)   until now, the dynamics of  the  public  financial  sector  has undergone  a  definite  change due to the different  facts faced by each  time.   In  its development there   are  fixed  and some  are  changing. This study is use literature review method, literature review is a study conducted by researchers by collecting a number of books, magazines related to problems and research purposes. Develop  a sense of    social   responsibility  in  people who  have  excess  wealth. Zakat  is a mandatory  provision  in  the  economic  system so that  in its implementation is  carried out  through  official  or legal institutions.   Waqf recipients    from the  community are done   in an  easy way, among  others  through mobile banking, Short Message Service and  waqf kiosks.  In Malaysia  to  develop  waqf assets,   investments  are made  through  Malaysian sukuk and capital market instruments issued by the Securities  Commission  in  February  2001.